Compassionate Capitalism - The Pursuit of Equal Income Distribution (Asian Journal of Social Science Studies, 2017)
During the last decades, the great weaknesses of capitalism have flourished. Inequality of income distribution has worsened painfully, the gap between rich and poor widens more and more every day, and just a few lucky entrepreneurs in the world are able to enjoy the capital benefits of the global system. Hunger, poverty, demographic explosion, ageing, and unbridled mass migration, among other factors, have become critical social dilemmas directly related to capitalist deviations, all of which cause us to foresee a chaotic world scenario in the near future. The numbers shown in this article confirm that the world’s economic disparity, instead of diminishing, is increasing at an alarming rate. Unfortunately, since the world economy completely depends on capitalism, this system is still extremely powerful and influential in global decision-making, thus further aggravating economic disparity. Therefore, as it is not possible to avoid the capitalist system, we will make proposals that are feasible for implementing within the current capitalist tendencies in order to alleviate global imbalance. Compassionate Capitalism is an alternative that promotes flexibilization of the system in order to make it more sustainable. It seeks to diminish corporate control over the economy and markets by regaining the State’s economic intervention so that profits are fairly redistributed for the common welfare. The information used for the study is based on the most recent international reports and global circumstances of the topics in question.